A project proposal for the formation of People’s Theatre : a community drama project for the moral development and empowerment of the youth in Hout Bay - Bastani, Nava Corinne (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (School of Public Management and Planning))--University of Stellenbosch, 2007.